HUBUNGAN KEMAMPUAN KOGNITIF, NILAI BUDAYA, GAYA HIDUP DENGAN EMPATI LINGKUNGAN PADA MASYARAKATWILAYAH SUNGAI PEMBUANGAN LIMBAH BATIK Survei pada Masyarakat Kota Batik Surakarta - Peduk Rintayati (Program Studi Pendidikan Kependudukan dan Lingkungan Hidup, 2011)
AbstractThe objective of this research is to study the relationship between cognitive ability, cultural value, and lifestyle with the environment empathy towards the society in the batik waste disposal area.The research was conducted in the community of batik waste disposal area. The sample was taken by using random sampling technique.The data for the environmental empathy, cognitive ability, value of culture, and lifestyle were gathered by using questionnaire. The data obtained was analyzed by using regression, simple correlation, multiple correlation, and partial correlation.The result of the study showed that: (1) there was a positive correlation between the cognitive ability with environmental empathy; (2) the was a positive correlation between the value of culture with the environmental empathy; (3) there was a positive correlation between lifestyle with the environmental empathy; (4) there was a positive correlation between cognitive ability, value of culture, and lifestyle with the environmental study.It can be concluded that cognitive ability, value of culture, and lifestyle can increase the envirionmental empathy.